Solvent-free Microwave-assisted Synthesis of 1-(1,3-diphenyl-1H-pyrazol- 4-yl)-3-(2-hydroxyphenyl) Propane-1,3-dione Using K2CO3 as Green Solid Support - Dhokale, Namdeo T.; Kale, Satish B.; Nagre, Sadashiv S.; Konda, Shankaraiah G.; Dalvi, Navanath R. (Letters in Organic Chemistry, 2023)
We herein present the synthesis of 1-(1,3-diphenyl-1H-pyrazol-4-yl)-3-(2-hydroxysubstituted phenyl) propane-1,3-dione using microwave irradiation. Reactions were carried out by employing a solvent-free path using K2CO3 as green solid support. The results were compared with those of the conventional method. This microwave-assisted synthesis avoids hazardous solvents and reduces the number of steps and time, providing increased yields. The synthesized products were characterized by IR, 1H NMR, and mass spectrometry.
Keywords: K2CO3